2015
DOI: 10.1002/acn3.168
|View full text |Cite
|
Sign up to set email alerts
|

Short pulse width widens the therapeutic window of subthalamic neurostimulation

Abstract: We explored the impact of pulse durations <60 μsec on the therapeutic window of subthalamic neurostimulation in Parkinson's disease. Current thresholds for full rigidity control and first muscle contractions were evaluated at pulse durations between 20 and 120 μsec during a monopolar review session in four patients. The average therapeutic window was 2.16 mA at 60 μsec, which proportionally increased by 182% at 30 μsec, while decreasing by 46% at 120 μsec. Measured chronaxies and model data suggest, that pulse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
145
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 132 publications
(156 citation statements)
references
References 24 publications
9
145
0
2
Order By: Relevance
“…5). As previously suggested, a shorter pulse duration of 560 ms could constitute an alternative approach of selectively stimulating dentato-thalamic fibres close to the DBS lead based on divergent chronaxies of different subthalamic fibre tracts (Reich et al, 2015).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…5). As previously suggested, a shorter pulse duration of 560 ms could constitute an alternative approach of selectively stimulating dentato-thalamic fibres close to the DBS lead based on divergent chronaxies of different subthalamic fibre tracts (Reich et al, 2015).…”
Section: Discussionmentioning
confidence: 96%
“…However, it was recently shown that VTA mirrored such neuronal proprieties as clinically defined (i.e. chronaxies) (Reich et al, 2015). Finally, VTA assumes that the primary effect of DBS is to activate myelinated axons, which was proved by several studies (Holsheimer et al, 2000;Paxinos and Mai, 2004;Groppa et al, 2014).…”
Section: Discussionmentioning
confidence: 97%
“…While the authors were not able to stimulate at pulse widths shorter than 60 µs, they were able to conclude that a stimulation pulse width closer to the chronaxie of tremor suppression would provide a wider therapeutic window between tremor relief and induction of side effects such as ataxia (15). Following this, Reich et al used model derived strength-duration curves for STN stimulation in PD patients to demonstrate a widening difference in the action potential initiation thresholds between small diameter fibres close to the electrode and larger diameter fibres further away, thought to correspond to therapeutic effects and adverse effects respectively (14).…”
Section: Discussionmentioning
confidence: 99%
“…They also noted that despite using a higher stimulation current at lower PWs, the energy used in terms of charge per pulse was actually lower than at 60µs. However, efficacy thresholds could not be determined in many patients at PWs below 30µs due to the need for very high stimulation current (14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation